Clinical characteristics of skin pigmentation caused by pemetrexed: a case report and literature review - Zhou, Leling; Chen, Li; Cao, Xin; Wang, Ying; Jiang, Ting (Frontiers in Medicine, 2025)
Pemetrexed demonstrates significant efficacy and safety in second-line and single-agent maintenance therapies, and in combination with platinum-based chemotherapy, it serves as the standard first-line treatment for driver-negative advanced non-small cell lung cancer (NSCLC). Although several studies have reported its widespread use and associated adverse effects, reports of pemetrexed-related pigmentation are rare. At present, the mechanism underlying pemetrexed-induced pigmentation remains unknown, and the timing of onset and risk factors are unclear. Here, we report a case of left lung adenocarcinoma (cT2bN2M1 IVB) with bone metastasis. After the third cycle of pemetrexed, pigmentation, numbness, pain, and walking difficulty developed on both feet and the dorsum of the ankles. These symptoms gradually worsened with subsequent chemotherapy cycles. Following neurotrophic treatment with diclofenac sodium gel and mecobalamin, numbness and pain improved, while pigmentation subsided gradually after discontinuation of pemetrexed. In addition, this study retrospectively analyzed nine patients with pemetrexed-induced skin pigmentation and found that the median onset was during the second cycle (range: 1–17 cycles). Pigmentation could be widely distributed on the body surface and aggravated with continued pemetrexed therapy. However, pigmentation resolved spontaneously after discontinuation, with individual differences.